Effects of estradiol on dopaminergic synapse formation in the mouse olfactory bulb. Issue 4 (15th December 2022) - Kiyokage, Emi; Ichikawa, Satoshi; Horie, Sawa; Hayashi, Shuichi; Toida, Kazunori
Abstract: Olfactory glomeruli are the sites of initial synaptic integration in olfactory information processing. They are surrounded by juxtaglomerular (JG) cells, which include periglomerular, superficial short axon, and external tufted cells. A subpopulation of JG cells expresses the dopamine synthetic enzymes, tyrosine hydroxylase (TH), and aromatic l ‐amino acid decarboxylase (AADC). TH cells corelease γ‐aminobutyric acid (GABA) and their processes extend to multiple glomeruli forming intra‐ and interglomerular circuits. It is well established that 17β‐estradiol (E2) exerts wide ranging effects in the central nervous system. However, participation of E2 in the modulation of neurotransmission and synaptic plasticity of TH cells in olfactory glomeruli is unknown. To address this, we subcutaneously implanted a 60‐day release pellet of E2 or placebo into intact male mice and compared glomerular TH, AADC, and vesicular γ‐aminobutyric acid transporter (VGAT) immunoreactivity between them. High‐voltage electron microscopy (HVEM) and ultra‐HVEM using immunogold revealed significantly increased immunoreactive intensity at the cellular level for TH and AADC after E2 treatment and for VGAT in TH cells. These results indicate that E2 may affect the interplay between dopaminergic and GABAergic systems. Moreover, random‐section electron microscopy analysis showed a significant increase in the number of symmetrical synapses from TH cell to mitral/tufted cell dendrites after E2 treatment. This result was supported by quantitative immunofluorescence staining with synapse markers. Together, these data indicate that E2 may regulate inhibition between TH cells and olfactory bulb neurons within the glomerulus via interaction between dopaminergic and GABAergic systems, thereby contributing to neuromodulation of odor information processing. Abstract : Summary scheme by quantitative EM/HVEM analysis shows effects of 17β‐estradiol (E2) on TH and VGAT immunoreactivity, and the synaptic organization of TH cell. E2 treatment significantly increases TH and VGAT immunoreactivity, and the number of symmetrical synapses from TH cells to mitral/tufted (M/T) cell dendrites. HVEM, high‐voltage electron microscopy; TH, tyrosine hydroxylase; VGAT, vesicular γ‐aminobutyric acid transporter; ON, olfactory nerve; red arrows, asymmetrical synapses; blue arrows, symmetrical synapses; ellipse (blue outline), flattened vesicle expressing VGAT.